a)
[tex]\frac{\frac{1}{4}-\frac{1}{3}-\frac{1}{6} }{\frac{1}{8}-\frac{1}{5}-\frac{1}{10} } =\frac{\frac{3}{12}-\frac{4}{12}-\frac{2}{12} }{\frac{5}{40}-\frac{8}{40} -\frac{4}{40} } =\frac{-\frac{3}{12} }{-\frac{7}{40} }=\frac{1}{4}*\frac{40}{7} =\frac{10}{7}=1\frac{3}{7}[/tex]Odpowiedź:
b)
[tex]\frac{\frac{9}{5}*\frac{7}{3} -\frac{15}{4}*\frac{2}{5} }{\frac{21}{4}*\frac{3}{7} }=\frac{\frac{21}{5} -\frac{6}{4} }{\frac{9}{4} }=\frac{54}{20} *\frac{4}{9} =\frac{6}{5} =1,2[/tex]
c)
[tex]\frac{1\frac{1}{2} +2\frac{1}{4}-\frac{2}{3}*\frac{3}{2} }{\frac{1}{4}*4-\frac{22}{7}*\frac{7}{11} }=\frac{3\frac{3}{4}-1 }{1-2} =\frac{2\frac{3}{4} }{-1} =\frac{11}{4}*(-1)=-2,25[/tex]